Non-Adaptive Methods for Fetal ECG Signal Processing: A Review and Appraisal - Jaros, Rene; Martinek, Radek; Kahankova, Radana (Sensors (Basel, Switzerland), 2018)
Fetal electrocardiography is among the most promising methods of modern electronic fetal monitoring. However, before they can be fully deployed in the clinical practice as a gold standard, the challenges associated with the signal quality must be solved. During the last two decades, a great amount of articles dealing with improving the quality of the fetal electrocardiogram signal acquired from the abdominal recordings have been introduced. This article aims to present an extensive literature survey of different non-adaptive signal processing methods applied for fetal electrocardiogram extraction and enhancement. It is limiting that a different non-adaptive method works well for each type of signal, but independent component analysis, principal component analysis and wavelet transforms are the most commonly published methods of signal processing and have good accuracy and speed of algorithms.
Keywords: Electrocardiography; Electrodes; non-adaptive filtering; Wavelet Analysis; elektrokardiografie; Fetus; analýza hlavních komponent; algoritmy; počítačové zpracování signálu; elektrody; Principal Component Analysis; fetal monitoring; plod; lidé; Humans; digital signal processing; fetal electrocardiogram extraction; Algorithms; Signal Processing, Computer-Assisted; vlnková analýza